Safety of Dexamethasone for Nausea and Vomiting Prophylaxis in Children Receiving Hematopoietic Stem Cell Transplantation. Issue 5 (July 2018) - Paw Cho Sing, Edric; Schechter, Tal; Ali, Muhammad; Sung, Lillian; Dupuis, L. Lee
Abstract : Background: Many children undergoing hematopoietic stem cell transplantation (HSCT) experience chemotherapy-induced nausea and vomiting (CINV) despite receiving prophylaxis. Guideline-consistent CINV prophylaxis includes dexamethasone, but uncertainty with regard to safety potentially limits the use of dexamethasone in children. We describe immediate adverse events (AEs) attributable to dexamethasone given for CINV prophylaxis to children during HSCT conditioning. Materials and Methods: Children enrolled in a previous prospective study were retrospectively analyzed. Objective parameters related to specific AEs occurring within 5 days of dexamethasone administration were abstracted from health records and graded according to the Common Terminology Criteria for Adverse Events version 4.03 (CTCAE v4.03). Their association to dexamethasone was assessed using the Liverpool Causality Assessment Tool. Results: Forty-six children (median age, 10.2 y) were eligible for analysis. The most frequent AEs attributable to dexamethasone (Liverpool Causality Assessment Tool category of probable or definite ) were hyperglycemia (63%; CTCAE v4.03 grade 3: 2%), hypertension (52%; CTCAE v4.03 grade 3: 15%), and bradycardia (46%; CTCAE v4.03 grade 3: 0%). Other AEs included dyspepsia or gastroesophageal reflux disease (24%) and alterations in mood and behavior (9%). No AE exceeded CTCAE v4.03 grade 3 in severity. Conclusions: In children undergoing HSCT who received dexamethasone for CINV prophylaxis, immediate AEs attributable to dexamethasone were most often of minor clinical importance and transient. Abstract : Supplemental Digital Content is available in the text.